14-3-3 Proteins and a 13-lipoxygenase form associations in a phosphorylation-dependent manner. (December 2000) - Holtman, W. L.; Roberts, M. R.; Wang, M.
Abstract : Recently, we have demonstrated by two different methods that lipoxgenases (LOXs) and 14-3-3 proteins form interactions in barley embryos [Holtman, Roberts, Oppedijk, Testerink, van Zeij] and Wang (2000) FEBS Lett. 474, 48–52]. It was shown by both co-immunoprecipitations and surface-plasmon resonance experiments that 13-LOX, but not 9-LOX, forms interactions with 14-3-3 proteins. In the present report we show that the presence of 13-LOX and 14-3-3 proteins was established in high-molecular-mass complexes. Amounts of 13-LOX and 14-3-3 proteins in high-molecular-mass fractions increased during germination, but were reduced after dephosphorylation of protein extracts or competition with the 14-3-3-binding peptide P-Raf-259, indicating that 13-LOX and 14-3-3 proteins interact in a phosphorylation-dependent manner.